STRATEGI MANAJEMEN KURIKULUM VOKASI DALAM MENINGKATKAN KOMPETENSI DAN DAYA SAING LULUSAN - Mufidah Amalia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The development of vocational curriculum at the senior high school (SMA) level represents a strategic response to the increasing demand for graduate competence and competitiveness aligned with the needs of business and industry (DUDI). The vocational program at SMA Nahdlatul Ulama 1 Gresik was initiated based on community aspirations and local industry demands, while also accommodating students’ interests and talents. This study aims to analyze the curriculum management strategies implemented to enhance students’ competencies and graduate competitiveness. The research employed a qualitative approach with a case study design, involving the principal, vocational teachers, students, parents, community members, and industry partners as informants. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that curriculum management strategies were carried out through industry-based planning, gradual development of vocational expertise programs in response to labor market dynamics, strengthened partnerships with business and industry sectors, and continuous quality-based evaluation. These strategies contributed to the enhancement of students’ technical competencies and soft skills, as well as improving graduates’ work readiness and entrepreneurial capacity. The study concludes that adaptive, participatory, and industry-oriented vocational curriculum management is a key factor in improving the relevance and competitiveness of graduates in vocational-based senior high schools. ABSTRAK Pengembangan kurikulum vokasi di jenjang Sekolah Menengah Atas (SMA) merupakan respons terhadap tuntutan peningkatan kompetensi dan daya saing lulusan yang selaras dengan kebutuhan dunia usaha dan dunia industri (DUDI). Program vokasi di SMA Nahdlatul Ulama 1 Gresik lahir dari aspirasi masyarakat dan kebutuhan industri lokal serta sebagai upaya mewadahi minat dan bakat siswa. Penelitian ini bertujuan menganalisis strategi manajemen kurikulum vokasi dalam meningkatkan kompetensi dan daya saing lulusan. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, melibatkan kepala sekolah, guru vokasi, siswa, wali murid, masyarakat sekitar, dan mitra industri sebagai informan. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa strategi manajemen dilakukan melalui perencanaan berbasis kebutuhan industri, pengembangan program keahlian secara bertahap sesuai dinamika pasar kerja, penguatan kemitraan dengan DUDI, serta evaluasi berkelanjutan berbasis mutu. Strategi tersebut berkontribusi pada penguatan kompetensi teknis dan soft skills siswa serta meningkatkan kesiapan kerja dan kewirausahaan lulusan. Penelitian ini menyimpulkan bahwa manajemen kurikulum vokasi yang adaptif, partisipatif, dan berbasis kebutuhan industri menjadi faktor kunci dalam meningkatkan relevansi dan daya saing lulusan SMA berbasis vokasi.